Epicardial atherosclerosis and coronary tortuosity in patients with acetylcholine-induced coronary spasm. Issue 1 (3rd November 2022) - McChord, Johanna; Gollwitzer, Robert; Seitz, Andreas; Sechtem, Udo; Bekeredjian, Raffi; Ong, Peter
Abstract : Background: Angina pectoris in the absence of relevant epicardial stenoses is frequently caused by coronary spasm. This mechanism of angina is common yet underdiagnosed in daily clinical practice. The pathophysiology of coronary spasm is complex, multifactorial, and not completely understood. The purpose of this study was to analyze the relationship between macroscopic coronary morphologies and coronary spasm. Methods: Epicardial atherosclerosis, coronary vessel tortuosity, coronary aneurysms, and myocardial bridges were analyzed angiographically in 610 patients and a potential association with the result of an intracoronary acetylcholine (ACh) provocation test was investigated. Results: The comparison showed that angiographic morphologic variations in the coronary arteries are related to the occurrence of coronary spasm. We observed a strong association between the presence of epicardial atherosclerosis and epicardial spasm [87 patients of 179 with epicardial spasm had epicardial atherosclerosis (49%) vs. 45 patients of 172 with microvascular spasm (26%) vs. 89 patients of 259 with negative/inconclusive ACh test (36%); P < 0.005]. Moreover, we found a higher frequency of coronary tortuosity in patients with microvascular spasm [99 patients of 172 with microvascular spasm had at least moderate coronary tortuosity (58%) vs. 76 patients of 179 with epicardial spasm (43%) vs. 126 patients of 259 with negative/inconclusive ACh test (49%); P = 0.017]. Multivariable analysis revealed epicardial atherosclerosis (<50% stenosis) on coronary angiography as a predictor for epicardial spasm (OR, 2.096; 95% CI, 1.467–2.995; P < 0.0005). Female sex (OR, 5.469; 95% CI, 3.433–8.713; P < 0.0005), and exertional angina (OR, 2.411; 95% CI, 1.597–3.639; P < 0.0005) were predictors of microvascular spasm in multivariable analysis. Conclusion: In angina patients with no obstructive coronary artery disease, epicardial atherosclerosis is associated with ACh-induced epicardial coronary spasm. Moreover, coronary microvascular spasm is more prevalent in female patients and those with exertional angina. Our results provide insights into the relationship between coronary morphology and coronary vasomotor function.